ANALISIS SUMBER DAYA DAN KAPABILITAS PT BANK TABUNGAN NEGARA (PERSERO) Tbk. DENGAN PENDEKATAN RESAURCE BASED VIEW (REV) - , Nina Fasichach ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High demand of the housing has opened enormous opportunities in industrial property in Indonesia. This opportunity is also became attraction for banks in Indonesia to use Home Ownership Loan (mortgage/KPR) product as a priority product of its businesses. Bank BTN as the first pioneer banks which provide KPR facilities faces competition in the KPR sector automatically. To face the challenge, Bank BTN needs to know and utilize the resources and capabilities to achieve sustainable competitive advantage. The analysis tool in this research uses Resource-Based View (RBV) approach with VRIO framework, which consists of valuable, rare, imperfectly imitable, and organization. The RBV approach is able to identify the potential resource and capability as a company's internal strengths to achieve sustainable competitive advantage. The research result has identified ten resources and capabilities which are possessed by Bank BTN. Six of them meet VRIO framework, therefore it could be used as a source of sustainable competitive advantage. They are corporate experiences, employees who have experience and competence and loyal to the company, good relationships with shareholders and partnership with stakeholders, good relationships between employees, database and information, and corporate culture. And four of them did not meet the VRIO framework, are buildings and office equipments, systems (business application programs) and main server, brand and reputation, and managerial capabilities of management.